Identifying and tracking climate change mitigation strategies with a cluster-based assessment - Filippo Maria D’Arcangelo; Tobias Kruse; Mauro Pisu (npj Climate Action, 2024)
Abstract To guide climate change mitigation efforts, we identify and characterize the different types of mitigation strategies countries adopted over the last two decades. The analysis exploits the novel and rich policy repository of the OECD’s Climate Actions and Policies Measurement Framework (CAPMF), covering more than 120 policy variables and 50 countries over 2000–2020. All countries in the dataset increased the number of climate policy instruments and their stringency over the past two decades, but at a different pace and using different policy instruments. Using statistical cluster analysis, we identify four distinct types of mitigation strategies, which differ in the composition and stringency of mitigation policies. Regression results show that emissions are negatively associated with the overall stringency of the country’s mitigation strategies. Evidence also supports the hypothesis that this relationship is stronger for mitigation strategies comprising a more diverse set of instruments, pointing to possible policy synergies.